Effect of Silt and Clay Fraction Content on Frost Heave of Fine-Grained Soils - WITEK-ZIELONKA Kinga; PARYLAK Krzysztof; KILIAN Wojciech; ZIELONKA Łukasz (Architecture, Civil Engineering, Environment)
Frost heave in soils is a significant problem of geotechnical engineering. Despite the introduction of numerous simplified frost susceptibility criteria, there is still no clear relationship between the particle size distribution and their frost heaving susceptibility. Therefore, an experimental attempt was made to link the graining features of the four soils with the mechanisms of the formation of frost heave. The main aim of the study is to determine the influence of the content of silt and clay fractions on the height of the frost heave. The tested soils were characterized by a varied content of the silt fraction, which, together with smaller ones, amounted to 30%, 40%, 50% and 70%, and a variable content of the clay fraction amounting to 0%, 0%, 21% and 5% in individual soils, respectively. For the purposes of the experiment, a test stand was constructed that allows for testing 6 identical samples at a time. The tests were carried out in an open-system test, i.e. with the possibility of water flowing into the freezing zone. The total freezing process was carried out at -10°C and lasted 160 hours. On the basis of the obtained results of the increase in the height of the samples, it was shown that the silt with the highest total content of silt and clay fractions of 70% shows the highest frost heave and the smallest increase in the height of the samples in the freezing process is shown by sandy silt with the lowest sum of both these fractions. On the basis of the analysis of the results of the tested soils, it was found that the height of the frost heave was influenced by the presence of the clay fraction, but in connection with the presence of the silt fraction. In the frost heave soils, the content of the silt fraction influences the amount of the frost heave to the extent of more than two times smaller than the content of the clay fraction.